Culture Content based on Traditional Culture resources in the Andong area (Journal of Oriental Studies, 2023)
Using historical and cultural resources in city branding and marketing is gaining importance for local governments. Historical and cultural resources reflect daily life and culture, making them relatable and familiar to the public and offering differentiated regional cultural marketing opportunities. The need for establishing norms and methodologies for content development using cultural resources has led to the concept of digital cultural heritage and resources. Collaboration between local governments or organizations and media-specialized creators is essential for producing cultural heritage-based content that can illuminate the value of cultural heritage. The case of the Andong region demonstrates the potential of cultural heritage-based content in enhancing the value of historical and cultural resources.Keywords: Culture Content, Cultural Heritage, Traditional Culture, Andong, Knowledge, information hierarchy